A retrospective analysis of melioidosis in Cambodian children, 2009–2013. Issue 1 (December 2016) - Turner, Paul; Kloprogge, Sabine; Miliya, Thyl; Soeng, Sona; Tan, Pisey; Sar, Poda; Yos, Pagnarith; Moore, Catrin; Wuthiekanun, Vanaporn; Limmathurotsakul, Direk; Turner, Claudia; Day, Nicholas; et al.
Abstract Background Melioidiosis, infection byBurkholderia pseudomallei, is an important but frequently under-recognised cause of morbidity and mortality in Southeast Asia and elsewhere in the tropics. Data on the epidemiology of paediatric melioidosis in Cambodia are extremely limited. Methods Culture-positive melioidosis cases presenting to Angkor Hospital for Children, a non-governmental paediatric hospital located in Siem Reap, Northern Cambodia, between 1st January 2009 and 31st December 2013 were identified by searches of hospital and laboratory databases and logbooks. Results One hundred seventy-three evaluable cases were identified, presenting from eight provinces. For Siem Reap province, the median commune level incidence was estimated to be 28-35 cases per 100, 000 children <15 years per year. Most cases presented during the wet season, May to October. The median age at presentation was 5.7 years (range 8 days–15.9 years). Apart from undernutrition, co-morbidities were rare. Three quarters (131/173) of the children had localised infection, most commonly skin/soft tissue infection (60 cases) or suppurative parotitis (51 cases). There were 39 children withB. pseudomallei bacteraemia: 29 (74.4%) of these had clinical and/or radiological evidence of pneumonia. Overall mortality was 16.8% (29/173) with mortality in bacteraemic cases of 71.8% (28/39). At least seven children did not receive an antimicrobial with activity againstB. pseudomallei prior to death. Conclusions This retrospective study demonstrated a considerable burden of melioidosis in Cambodian children. Given the high mortality associated with bacteraemic infection, there is an urgent need for greater awareness amongst healthcare professionals in Cambodia and other countries where melioidosis is known or suspected to be endemic. Empiric treatment guidelines should ensure suspected cases are treated early with appropriate antimicrobials.